Web-Based Laptop Sparepart Information System : Sistem Informasi Penjualan Sparepart Laptop Berbasis Web - Soni Abdala; Mochamad Alfan Rosid (Universitas Muhammadiyah Sidoarjo, 2021)
In the current digital era, with the advancement of an era where technology is progressing rapidlyto facilitate the activities of the Indonesian people incommunicating.Where at this time many people make buying and selling transaction online so that people are just waiting for the arrival of the goods purchased.From here, many entrepreneurs take advantage of entrepreneurial opportunitieswith this online method, making it easier for people to buy and sell transactions and new business ideas.The purpose of making this web-based system is to make it easier for sellers and buyers, ordering an item and providing information on the existence of spare parts with several types and prices listed as well as available stock. In this data collection method, it is done by analyzing the system that is running to find out the weaknesses of the system.In this research, an application has been produced that can make it easier for HD Comp customers to make spare parts transactions easily for HD Comp parties for data management from transaction data carried out. The application runs smoothly and without problems. The benefits of this research are for future reference materials.